Complex Involvement of Interleukin-26 in Bacterial Lung Infection - Che, Karlhans F.; Paulsson, Magnus; Piersiala, Krzysztof; Sax, Jakob; Mboob, Ibrahim; Rahman, Mizanur; Rekha, Rokeya S.; Säfholm, Jesper; Adner, Mikael; Bergman, Peter; Cardell, Lars-Olaf; Riesbeck, Kristian; et al. (Frontiers in Immunology, 2021)
Pneumonia is a global cause of mortality, and this provides a strong incentive to improve the mechanistic understanding of innate immune responses in the lungs. Here, we characterized the involvement of the cytokine interleukin (IL)-26 in bacterial lung infection. We observed markedly increased concentrations of IL-26 in lower airway samples from patients with bacterial pneumonia and these correlated with blood neutrophil concentrations. Moreover, pathogen-associated molecular patterns (PAMPs) from both Gram-negative and -positive bacteria increased extracellular IL-26 concentrations in conditioned media from human models of alveolar epithelial cells, macrophages, and neutrophils in vitro. Stimulation with IL-26 inhibited the inherent release of neutrophil elastase and myeloperoxidase in unexposed neutrophils. This stimulation also inhibited the expression of activity makers in neutrophils exposed to Klebsiella pneumoniae. In addition, priming of human lung tissue ex vivo with exogenous IL-26 potentiated the endotoxin-induced increase in mRNA for other cytokines involved in the innate immune response, including the master Th17-regulator IL-23 and the archetype inhibitory cytokine IL-10. Finally, neutralization of endogenous IL-26 clearly increased the growth of Klebsiella pneumoniae in the macrophage culture. These findings suggest that IL-26 is involved in bacterial lung infection in a complex manner, by modulating critical aspects of innate immune responses locally and systemically in a seemingly purposeful manner and by contributing to the killing of bacteria in a way that resembles an antimicrobial peptide. Thus, IL-26 displays both diagnostic and therapeutic potential in pneumonia and deserves to be further evaluated in these respects.